Parents’ Attitude towards Community Schools and its Influence in the Choice of Schools for Their Children - Chaulagai, Sangam (International Research Journal of MMC, 2023)
This study has explored parents’ attitude towards community schools and its influence in the choice of schools for their children. Selection of school is directly associated with quality education and academic excellence of children that ultimately affect their future careers. Privatisation in education has provided options for parents to select either community or private schools for their children. This study analysed and interpreted data from a neoliberal perspective employing a qualitative research design. The data were collected through interviews and observations from two community and two private schools representatively. Ten parents, who were selected purposively from those four schools and four headteachers of those schools were the participants of this study. The study found that parents generally had negative attitude towards community schools, but some of the community schools had been able to change the attitude of parents towards community schools. The effect of the neoliberal culture could be seen among the parents which played a significant role in parents' decision of choosing schools to enroll their children. Hence, the study concluded that parents’ negative attitude towards community schools have affected the selection of schools for their children in Nepal.